A Review of Fibrocartilaginous Embolic Myelopathy and Different Types of Peracute Non-Compressive Intervertebral Disk Extrusions in Dogs and Cats - De Risio, Luisa (Frontiers in Veterinary Science, 2015)
This review discusses terminology, pathological, clinical, and magnetic resonance imaging (MRI) findings, treatment, outcome, and prognostic factors of fibrocartilaginous embolic myelopathy (FCEM), acute non-compressive nucleus pulposus extrusion (ANNPE), and intradural/intramedullary intervertebral disk extrusion (IIVDE). FCEM, ANNPE, and IIVDE have a similar clinical presentation characterized by peracute onset of neurological dysfunction that is generally non-progressive after the initial 24–48 h. Differentiating between these conditions can be challenging, however, certain clinical and imaging findings can help. FCEM can occur in both adult and immature animals, whereas ANNPE or IIVDE have been reported only in animals older than 1 year. In dogs, ANNPE and IIVDE most commonly occur in the intervertebral disk spaces between T12 and L2, whereas FCEM has not such site predilection. In cats, FCEM occurs more frequently in the cervical spinal cord than in other locations. Data on cats with ANNPE and IIVDE are limited. Optimal MRI definition and experience in neuroimaging can help identify the findings that allow differentiation between FCEM, ANNPE, and IIVDE. In animals with ANNPE and IIVDE, the affected intervertebral disk space is often narrowed and the focal area of intramedullary hyperintensity on T2-weighted images is located above the affected intervertebral disk space. In dogs with ANNPE signal changes associated with the extruded nucleus pulposus and epidural fat disruption can be identified in the epidural space dorsal to the affected intervertebral disk. Identification of a linear tract (predominantly hyperintense on T2-weighted images, iso to hypointense on T1-weighted images and hypointense on T2*-weighted gradient recall echo images) extending from the intervertebral disk into the spinal cord parenchyma is highly suggestive of IIVDE. Treatment of FCEM and ANNPE is conservative. Dogs reported with IIVDE have been managed either conservatively or surgically. Prognostic factors include degree of neurological dysfunction (particularly loss of nociception) and disease-specific MRI variables.